PENGARUH PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT DENGAN KOMPETENSI SEBAGAI VARIABEL MODERASI - Trisna Windika Windika Pratiwi, Ni Putu; Putu Ayu Kusumawati (KRISNA: Kumpulan Riset Akuntansi, 2024)
Audit quality has an important relationship with business sustainability because it can make financial reports trustworthy and become the basis for decision making and encourage increased business profitability. There are inconsistencies in the results of previous research on the influence of auditor experience on audit quality, so it is estimated that the competence of the auditor is able to moderate the relationship between the two. The aim of this research is to obtain empirical evidence regarding the influence of auditor experience on audit quality and to prove whether competence is able to moderate the relationship between auditor experience and audit quality. The population in this study were all auditors who worked at Public Accounting Firms (KAP) in Bali Province. The sampling method in this research was a non-probability sampling method with a purposive sampling technique, so that the number of respondents was 52 auditors. The data in this study was tested using the Moderated Regression Analysis (MRA) technique. The research results show that the auditor's experience has a positive effect on audit quality. The research results also found that competency was able to moderate the influence of experience on audit quality. Keywords: experience, competency, audit quality